Pemberdayaan Masyarakat Dalam Menanggulangi Kejadian Luar Biasa (KLB) Melalui Pendekatan Epidemiologi Komunitas - Musdalifah, Musdalifah; Yermi, Yermi; Adiaksa, Baso Witman; Harlina, Harlina; Pudyastuti, Rita Rena (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Extraordinary Events (KLB) are a serious threat to public health that require rapid and appropriate response. The active role of the community is crucial in early detection and response to outbreaks, particularly through a community epidemiology approach. This article discusses the implementation of a community epidemiology-based community empowerment program in outbreak-prone areas. Implementation methods included education, cadre training, outbreak response simulations, and citizen-based monitoring. Results showed increased community knowledge, community preparedness, and a reduction in delays in case reporting. The conclusion of this activity is that the community epidemiology approach is effective in building a community-based early detection and rapid response system.